The historical context of globalization in Egypt: Foreign professors’ migration to the Egyptian university (1908) - Hamed Abdelreheem Ead (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
As a major offshoot of the national Egyptian movement that goes back to the beginning of the 20th century, a number of national leaders, Enlightenment pioneers, and social thinkers called for the establishment of an Egyptian university. These individuals hoped for this to be a lighthouse of liberal thought and the basis of a comprehensive academic revival in all fields of knowledge in order to be able to cope with international scientific and academic advancement. By May 1908, the Royal Palace chose the administrative council for the project of the Egyptian University (EU). When the university began, not a single Egyptian could meet all its ideal criteria for professors. The EU did borrow staff from the schools of law for its criminology, economics, and law programs. Dar al-Ulum constructed the university between 1908and 1925, which had at least nine professors. The other source of interim professors was Europe. The European professors fall into two categories: those who lectured in French or English on topics unrelated to the Middle East and the orientalists who lectured on Arabic and Islamic subjects. France, Italy, England, and, to a lesser extent, Germany all jockeyed for influence at the university. European professors dominated the first generation of faculty members while promising that Egyptian students were sent abroad to train for future teaching positions. In the present review, light will be shed on the large role played by those elite European professors in determining and pushing the university forward to stand with the Egyptian professors in order to examine the development of European-style education within the EU and, to a lesser extent, the cultural influence of a number of European countries in Egyptian education.